Transaction governance and contractual relations in a transition economy: the case of Ukraine - Nashchekina, O. N.; Timoshenkov, Igor V. (My University, 2002)
The characteristics of a transitional institutional environment are identified and their implications for contractual relations are discussed. Empirical results illustrative of the peculiarities of the Ukrainian business environment and contractual relations in the Ukrainian small business are presented. The interplay between formal and informal arrangements in contractual relations is analyzed. The role of different types of trust in transaction governance is discussed.
Keywords: transition economy; institutions; small business; transaction governance; contractual relations; trust